2020
DOI: 10.1080/24740527.2020.1765692
|View full text |Cite
|
Sign up to set email alerts
|

Subacute pain trajectories following major musculoskeletal surgery in adolescents: A pilot study

Abstract: Background: Adolescents who undergo major surgery experience high rates of disabling acute and chronic postsurgical pain (CPSP). However, little is known about the subacute period when acute to chronic pain transition occurs. Aims: The aims of this study were to examine feasibility of electronic daily monitoring of pain and opioid use in adolescents during the first 30 days at home following major surgery and identify target features of subacute pain curves associated with CPSP at 4 months. Methods: Twenty-fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…2,3 Continued pain at home during the subacute period has been shown to significantly affect recovery. 4 In a wide range of inpatient surgeries, moderate to severe postsurgical pain at one month was independently associated with greater than three-fold higher odds of experiencing a clinically significant deterioration in both physical and psychosocial health, as well as in overall health-related quality of life after surgery. 5 When acute pain persists after surgery, it can develop into a chronic pain condition.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…2,3 Continued pain at home during the subacute period has been shown to significantly affect recovery. 4 In a wide range of inpatient surgeries, moderate to severe postsurgical pain at one month was independently associated with greater than three-fold higher odds of experiencing a clinically significant deterioration in both physical and psychosocial health, as well as in overall health-related quality of life after surgery. 5 When acute pain persists after surgery, it can develop into a chronic pain condition.…”
Section: Introductionmentioning
confidence: 92%
“…9,10,51 Looking beyond hospital discharge, studies examining recovery during the initial weeks at home identified significant relationships between subacute pain with subsequent chronic pain. 4,16,28 In general, studies have relied on self-report measures and data from the electronic medical record to assess acute recovery. Future studies should apply more granular monitoring (such as daily pain diaries) and employ objective measures (eg, actigraphy monitoring of activity, electronic medication monitoring of opioid use) to better capture acute recovery.…”
Section: Factors Related To Acute Postoperative Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…A trained researcher blind to group allocation conducted an established telephone interview previously used in pediatric surgical cohorts 14 , 15 to collect the ratings needed to calculate the memory biases 6 weeks postsurgery. Youth recalled both the sensory (i.e., pain intensity) and affective (i.e., pain unpleasantness and anxiety) aspects of their postsurgical pain at two time points when pain is typically most severe 36 : (1) on day 1 postsurgery and (2) during the acute recovery period (i.e., days 1 to 3 postsurgery); thus, acute recovery encompassed the first time point (i.e., day 1 after surgery). These time points have been used in previous postsurgical pain memory research.…”
Section: Methodsmentioning
confidence: 99%